Incidence of symptom-driven Coronary Angiographic procedures post-drug-eluting Balloon treatment of Coronary Artery drug-eluting stent in-stent Restenosis-does it matter? - Voon, Victor; Gumani, Dikshaini; Craig, Calvin; Cahill, Ciara; Mustafa, Khalid; Hennessy, Terry; Arnous, Samer; Kiernan, Thomas (Journal of Cardiology and Cardiovascular Medicine, 2017)
Objectives: The clinical impact of drug-eluting balloon (DEB) coronary intervention for drug-eluting in-stent restenosis (DES-ISR) is not fully known. To further evaluate this impact, we aimed to describe the incidence of symptom-driven coronary angiography (SDCA), an under-reported but potentially informative outcome metric in this cohort of patients. Methods: We retrospectively identified all patients (n=28) who had DEB-treated DES-ISR at University Hospital Limerick in between 2013-2015 and evaluated the incidence of subsequent SDCA as the primary endpoint. Data were expressed as mean ± SD and %. Results: Baseline demographics demonstrate a mean age 63±9 years with 61% of DEB-treated DES-ISR presenting with acute coronary syndrome. Mean number of ISR per patient and number of DEB per lesion was 1.2±0.6 lesions and 1.2±0.6 balloons, respectively. The incidence of SDCA was 54% after mean follow-up duration of 179±241 days. 67.8% of patients had follow-up data beyond 12 months. Within the first year of follow-up, the incidence of SDCA with and without target lesion revascularization (TLR) was 11% and 36% respectively. Among patients with SDCA without TLR, 30% had an acute coronary syndrome not requiring percutaneous coronary intervention. Conclusions: A high incidence of SDCA was observed, particularly within the first 12 months after DEB-treated DES-ISR. This under-reported metric may represent a cohort at higher cardiovascular risk but requires further confirmation in larger studies.